Islamic Identity Politics in The Novel Amina's Voice by Hena Khan (2017) Based on Kuntowijoyo’s Prophetic Literature Studies - Muiz Yusron Hamdi (Universitas Muhammadiyah Semarang, 2023)
This research aims to explain the views on Islamic identity politics in Amina’s Voice by Hena Khan (2017). The research theme was analyzed structurally using the Kuntowijoyo prophetic literature study approach. The discussion of prophetic literature is relevant to novel that express religious and universal values. The method used in this study is descriptive qualitative; describing the narrative in the novel and analyzing it with prophetic elements. This research explains that several prophetic literary principles emerge and messages voiced by the author through Amina, an American Muslim girl of Pakistani descent, voicing that Islam is a structure and a unified whole, upholding human values, togetherness in diversity, and rejecting discrimination and violence.